Scaling up and Sustainability:: the experience of rural India - Purushothaman, Seema; Abraham, Rosa (Sustainability in Debate, 2011)
From its genesis as a primarily ecological concept, the notion of sustainability has come a long way to encompass multiple dimensions, including cultural, social and economic. The modern-day emphasis on efficiency, profits and scaling up has posed threats to the multiple realms of sustainability. This paper provides insights into the conflicts between scaling up and sustainability in the agricultural sector in India. Using a graphical representation of sustainability, the paper illustrates the conflicts that are created when there is scaling up of one dimension. This graphical tool is used to illustrate the consequence of scaling up on overall sustainability in the context of rural India. It suggests alternative and more sustainable approaches to secure the livelihoods of the rural poor.